Hihg-Pressure of M2AX (211), M3AX2 (312) and M4AX3 (413) MAX phases, Sr2MWO6 (M = Ca, Cd, Co) Double Perovskites, SrNi3(P2O7)2 and NaCo(H2PO3)3.H2O phosphates, using angle dispersive X-ray diffraction and Raman Spectroscopy - Manoun, Bouchaib (Université Sidi Mohamed Ben Abdellah, Faculté des Sciences Dhar El Mehraz, Fès, 2006)
The present study reports on Angle Dispersive X-ray diffraction and Raman Spectroscopic High Pressure Studies of M2AX (211), M3AX2 (312) and M4AX3 (413) MAX phases, Sr2MWO6 (M = Ca, Cd, Co) Double Perovskites, SrNi3(P2O7)2 and NaCo(H2PO3)3.H2O phosphates. Up to a pressure of 55 GPa, no phase transformations were observed in the MAX phases. Based on the nature of the M, A or X element a large effect on the bulk moduli of the MAX phases was observed. The presence of X in the structure has a stablizing effect on the M-Al bonds, presumably by pulling electrons away from those bonds into the M-X bonds. The double perovskites Sr2MWO6 (M = Ca, Cd, Co) underwent a phase transition at 10.4 GPa, for Sr2CaWO6 and at 15 Gpa for Sr2CdWO6. Two phase transitions were observed in the case of the co-containing compound at about 2 and 11 GPa, the first transition is from tetragonal structure (14/m) to P21/nSr2CaWO6-like structure. A phase transition was observed in the pyrophosphate SrNi3(P2O7)2 at 50.5 GPa for, the new high pressure phase has a tetragonal symmetry. In NaCo(H2PO3)3.H2O phosphate an amorphization occurred at pressures higher than 7 GPa.
Keywords: MAX phase; Double Perovskite; Pyrophosphate; Dihydrogenphosphite; Synchrotron radiation; Raman spectroscopy; Chimie-Physique; High pressure; Sciences des matériaux; Diamond anvil cell